Pengaruh Pendidikan Kesehatan Terhadap Penerapan Self-Management Tentang Pencegahan Kekambuhan Penyakit Gastritis Di Wilayah Kerja Puskesmas Sentosa Baru Medan - Pardede, Fenni Veronika; Silaen, Harsudianto (Indonesian Trust Nursing Journal, 2024)
Gastritis occurs due to inflammation of the gastric mucosa caused by irritants and infections. The most important thing in treatment is the patient's ability to treat and manage the disease so that through self-management, ulcer sufferers can manage their disease independently by adopting healthy lifestyles so that they can prevent, control and reduce the risk of disease. This study aims to determine the effect of health education on the implementation of self-management regarding preventing recurrence of gastritis. This type of research is Quasi-experimental with a pre-posttest one group only design. The sample in this study was 48 people using purposive sampling techniques. The results of this research show that there is an influence of health education on the implementation of self-management regarding preventing recurrence of gastritis as seen from the results of the Wilcoxon signed rank test analysis with a value of Z= -5.752 showing a significance p value = 0.000 (p<0.05). It is concluded that there is an influence of health education on the application of self-management regarding the prevention of recurrence of gastritis in the working area of the Sentosa Baru Health Center in Medan.